Integrated Analysis of miRNA-mRNA Interaction Network in Porcine Granulosa Cells Undergoing Oxidative Stress. (4th November 2019) - Du, Xing; Li, Qiqi; Cao, Qiuyu; Wang, Siqi; Liu, Honglin; Li, Qifa
Abstract : Oxidative stress (OS), a common intracellular phenomenon induced by excess reactive oxygen species (ROS) generation, has been shown to be associated with mammalian ovarian follicular development blockage and granulosa cell (GC) impairment. However, the mechanism involved in these effects remains unknown, and the effect of OS on the transcriptome profiles in porcine GCs has not been fully characterized. In this study, we found that hydrogen peroxide-mediated oxidative stress induced porcine GC apoptosis and impaired cell viability. Moreover, RNA-seq analysis showed that oxidative stress induced dramatic changes in gene expression in porcine GCs. A total of 2025 differentially expressed genes (DEGs) were identified, including 1940 DEmRNAs and 55 DEmiRNAs. Functional annotation showed that the DEGs were mainly associated with cell states and function regulation. In addition, multiple hub genes ( FOXO1, SOD2, BMP2, DICER1, BCL2L11, FZD4, ssc-miR-424, and ssc-miR-27b ) were identified by constructing protein-protein interaction and DEmiRNA-DEmRNA regulatory networks. Furthermore, a gene-pathway-function coregulatory network was established and demonstrated that these hub genes were enriched in FoxO, TGF- β, Wnt, PIK3-Akt, MAPK, and cAMP signaling pathways, which play important roles in regulating cell apoptosis, cell proliferation, stress responses, and hormone secretion. The current research provides a comprehensive perspective of the effects of oxidative stress on porcine GCs and also identifies potential therapeutic targets for oxidative stress-induced female infertility.